Pengaruh Rasio Profitabilitas Terhadap Nilai Perusahaan Pada Industri Minyak dan Gas Bumi yang Terdaftar di Bursa Efek Indonesia Periode 2012 - 2016 - Venny Junica Utami (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2018)
The research object of the research is Oil and Gas Industry and obsrvation object from 2012 -2016 where the sample consist of 4 companies namely PT. Ratu Prabu Energi Tbk, PT. Elnusa Tbk, PT. Surya Esa Perkasa Tbk, and PT. Radiant Utama Interinsco Tbk. Based on result of research assisted by software SPSS 20 generated regression equation Y = - 2,296 x 10-11 + 0,055 X1 –  0,100 X2 + 0,641 X3+ e on the other side obtained simultane ously test independent variable (profitability ratio) have significant effect to dependent variable (Value of the Company) marked with Fhitung 4,149 > Ftabel 3,24, for independent and partially dependent influence that return on asset and return on equity not a significant effect to Value of the Company, while net profit margin has a significant effect to Value of the Company. The independent variable (profitability ratio) is able to influence the dependent variable (Value of the Company). Rated R Square 43,8%, while the remaining 56,2% explained other factors beyond the study models.  Key Word: Net Profit Margin, Return on Asset, Return on Equity